Relación entre la discrecionalidad presupuestaria y la ejecución de la inversión pública en transporte en la Región Loreto 2018 – 2022 - Piña del Aguila, Diego (2024)
Public investment in transportation is extremely important for the creation of transportation infrastructure, since it provides accessibility in remote areas, promoting interconnection and trade, generating greater opportunities for the population to get ahead, promoting economic and social development. In this sense, the research proposes as its main objective to determine the relationship between budgetary discretion and the execution of public investment in transportation in the Loreto region 2018-2022. Likewise, the research has been developed with a quantitative approach of a descriptive type, correlational and non-experimental design, which included as a study population the data of the Public budget according to the PIA, PIM and budget execution of the transport sector in Loreto during the period 2018-2022. The investigation determined that in 2021 the investment in transportation amounted to S/ 563,941,497 soles, this being the amount of greatest investment during the years of study. Likewise, it was found that the national government is the level of government that makes the greatest investment in the transport sector in the Loreto Region during the study period. On the other hand, the Pearson Correlation coefficient was identified equal to R=0.637 and the value of Sig. (bilateral)=0.000, this being less than 5%, resulting significant at 95%, it is concluded that there is a positive relationship between the budgetary discretion and the execution of public investment in transportation in the Loreto region 2018-2022. In other words, when there is positive budgetary discretion, investment in transport is expected to increase.